A Combustible Dust Cleaning Device and Application. Issue 2 (February 2020) - Li, Yanping; Li, Yong; Li, Yunqi; Fang, Liu
Abstract: Flammable fine dust is dangerous to working environment. It is harmful to the health of workers. In this paper, a high efficiency combustible dust cleaning device is proposed. Its water consumption is about 0.289 kg/m 3, and the removal rate of dust with particle size less than 5 m is higher than 99%. This new cleaning device can be used in coal conveying system of power plant and other workplaces.